Implementation of the Village Fund Allocation Policy in the Economic Empowerment of the Community in Golo Mori Village in 2019 - Sukarman, Sukarman (Budapest International Research and Critics University, 2021)
This study aims to determine the implementation of the Village Fund Allocation policy in community economic empowerment in the village of Golo Mori, how the impact of the Village Fund Allocation Policy in community economic empowerment. By using a qualitative approach method. Data collection techniques, documentation, observation and interviews. Based on the results of this study, it shows that Golo Mori Village is a village that has various types of aspects of social problems ranging from economic aspects, human resources, and community welfare. , 0.5063 is very lagging. So with the community economic empowerment program carried out by the Golo Mori village government, it has not had a significant impact on changes in improving economic, social and community resources.